PENERAPAN MEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KERAGAMAN ALAM INDONESIA KELAS VIII-G SMPN 18 SURABAYA - Anisa, Zulva Rizky; Rindawati; Ririn Fatayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve the learning outcomes of students in class VIII-G SMP Negeri 18 Surabaya in Social Studies (IPS) material on Indonesia's natural diversity through the application of interactive wordwall media. This study used a Collaborative Classroom Action Research (PTKK) approach with two cycles to evaluate the effectiveness of interactive media in improving students' achievement of Learning Objective Criteria (KKTP). Data collection techniques included formative tests, classroom observations, and interviews with Social Studies teachers. In the pre-cycle, which is seen from the End of Year Summative test (SAT), the average student score is 67.26 with only 32.35% of students reaching the Learning Objective Achievement Criteria (KKTP). The application of wordwall interactive media in cycle I led to an increase in the class average score to 78.23 and 76.47% of students reached the Criteria for Achieving Learning Objectives (KKTP). The results of cycle II showed greater progress with the class average score increasing to 82.06 and 88.23% of students reaching the Criteria for Achievement of Learning Objectives (KKTP). These findings suggest that wordwall interactive media, when combined with adaptive teaching strategies, is effective in improving student learning outcomes. This study recommends the application of similar interactive media in other subjects to improve student learning outcomes.